Insight into IELTS : - Jakeman, Vanessa (Cambridge University Press, 1999)
This book offers comprehensive preparation for the International English Language Testing System, known as IELTS. It also introduces to the types of communication tasks which they are likely to meet in an English-speaking study environment.